Drug treatment of COVID-19 infection. Issue 3 (14th May 2023) - Lui, Grace; Guaraldi, Giovanni
Abstract : Purpose of review: COVID-19 pandemic has caused more than 6.6 million deaths globally. Tremendous efforts have been committed for the development of new and repurposed drugs for the treatment of COVID-19. Although different international and national guidelines share consensus in the management of COVID-19 disease with different levels of severity, new challenges have emerged, steering the need for ongoing research in advancing the clinical management of COVID-19. Recent findings: This review focuses on recent data from randomized trials and postmarketing real-world evidence for the treatment of mild to moderate disease in the outpatient setting and patients hospitalized for COVID-19 with varying level of severity. Relevant data for treatment of the latest omicron sub-variants in people who received vaccination are presented. Challenges in special populations, including immunocompromised hosts, patients with renal failure and pregnant women, are also discussed. Summary: Treatment of COVID-19 should be personalized according to host characteristics, degree of severity and available treatment options.